La Práctica Pedagógica un Contexto de Resignificación en los Escenarios Educativos de los Estudiantes de Licenciatura en Educación Infantil. (Memorias Sifored - Encuentros Educación UAN, 2023)
At the current times the reflective practice in the initial teacher training, as a strategy for the reflection about the teaching assignment and the overview of the bachelor in the context of the Education in Colombia, it plays an essential role towards the development of the pedagogical practices from the former students in early childhood education programs. In the methodology, hermeneutics is used in the discourse analysis of teachers in training, tutors and practice teachers and accompanying teachers in the practice centers. In this analysis, it is essential to transform the often reductionist view of pedagogical experiences, and that future teachers manage to resolve their own fears due to the lack of practice and the need to acquire professional competencies. Regarding the objectives and subsequent conclusions, the importance of the development of reflective practice as an essential element for the professional and personal growth of students of Early Childhood Pedagogy is emphasized, as it will allow them to improve their teaching, adapt to diversity, connect theory and practice, and develop problem-solving skills and self-awareness, thus contributing to the quality and effectiveness of early childhood education in Colombia.
Keywords: Vocational Training; Reflexive Practice; Educational Scenarios; Early Childhood Pedagogy Degree; Pedagogical Practice